Th1/Th17 T cell Tissue-Resident Immunity Increases Protection, But Is Not Required in a Vaccine Strategy Against Genital Infection With Chlamydia trachomatis - Nguyen, Nina Dieu Nhien Tran; Guleed, Safia; Olsen, Anja Weinreich; Follmann, Frank; Christensen, Jan Pravsgaard; Dietrich, Jes (Frontiers in Immunology, 2021)
TThe requirement for vaccine-induced tissue-resident immunity for protection against one or repeated infections with Chlamydia trachomatis (C.t.) is still not fully resolved. In this study, our aim was to investigate to which degree tissue-resident Th1/Th17 T cells in the genital tract (GT) could add to the protection mediated by circulating immunity. Out of several mucosal vaccine strategies, a strategy termed SIM (for simultaneous intrauterine and parenteral immunization with CAF01 adjuvanted CTH522), was superior in generating genital tract tissue-resident Th1/Th17 T cell immunity. This led to a faster and stronger local CD4 T cell response post infection, consisting of multifunctional IFNγ/TNFα-producing Th1 T cells and IFNγ/TNFα/IL-17-producing Th17 T cells, and a faster recruitment of innate immune cells. Post infection, SIM animals showed an additional significant reduction in bacterial levels compared to mice having received only a parenteral vaccine. Nevertheless, the parenteral strategy reduced bacterial levels by 75%, and interestingly, post infection, these mice generated their own vaccine-derived genital tract tissue-resident memory Th1/Th17 T cells, which upon a subsequent infection showed as fast an activation in the genital tract, as observed in SIM mice. Furthermore, in contrast to after the first infection, both groups of mice now showed a similar infection-induced boost in local vaginal IgA and IgG titers. Thus, vaccine-induced resident immunity, generated pre-infection, led to an advantage in the response against the first infection, but not the second infection, suggesting that a parenteral vaccine strategy is a suitable vaccine strategy against infections with Chlamydia trachomatis.